Implementation of Pilates Exercises to Reduce Pain Scale in Low Back Pain Patient - Fitriani, Ade; Rosmiati, Mia (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Introduction: Low back pain or lower back pain is pain that occurs in the waist or buttocks area which usually persists for a long time. Working as a disabled person is the dominant cause of LBP, including the profession as a nurse. LBP is the third disease that often occurs in the world, including in Indonesia. Pain is a problem caused by LBP, so it will interfere with sufferers in carrying out daily activities. Pain is a term for a complex reaction caused by physiological reactions in the nervous system. Objective: This case study aims to reduce pain intensity in low back pain patients. Method: This research is in the form of a case study with a descriptive method with a nursing care approach which includes assessment, nursing diagnosis, nursing care plan, nursing implementation and nursing evaluation. Results: The results of the case study at the assessment stage showed that Ms. M with the problem that emerged was acute pain so the nursing diagnosis was obtained as acute pain related to a physiological injury agent (SDKI), with the criteria for decreased pain results (SLKI). The intervention used uses the Standard Nursing Intervention (SIKI). Conclusion: The intervention was carried out over four meetings. By using NRS (Numeric Rating Scale) and FPS (Face Pain Scale) measurements, after carrying out Pilates exercises, a decrease in pain was obtained with the result that there was a decrease in pain intensity from initially severe pain with a pain scale of 8 (0-10) to mild pain with a scale of pain 3 (0-10).